(untitled) (AACINI - International Journal of Industrial Engineering, 2021)
This paper describes a proposal of serious game that can be applied to the early years of the engineering career, which may unfold in a physical classroom or a virtual one with the appropriate design changes. This constitutes an innovative didactic strategy to reinforce the basic and most fundamental concepts that are needed in general engineering courses at UTN-FRSN. The ludic proposal is done within the scope of a research project. It aims at incorporating, remembering and retaining concepts through association and logic in a collaborative dynamic and a team challenge. There are rounds within each team; every one of the participants must unravel an unknown topic on a limited time frame by asking questions to their team. The apprehension of theoretical topics is intended by practicing teamwork, effective communication, time management, and leadership since the early stages of the career in order to have a well-rounded education for the future industrial engineers. Serious games foster attention and active learning, improve the interaction and participation between students and teachers, and they favor the development of knowledge and skills through experimentation. Particularly in the beginning of the career, in scenarios like the present health emergency, serious games are positive for students to have a place to get to know each other if they haven’t yet.